Nitrogen alleviates salinity toxicity in Solanum lycopersicum seedlings by regulating ROS homeostasis - Singh, Madhulika (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2019. Published by Elsevier Masson SAS.